One Hundred Strong: A Colloquium on Transforming Natural History Museums in the Twenty‐first Century. (5th April 2013) - Watson, Bill; Werb, Shari Rosenstein
Abstract In February 2012, the Smithsonian's National Museum of Natural History (NMNH) convened 100 colleagues from 43 organizations to initiate a collaborative learning research agenda focused on examining important areas for innovation to better serve twenty‐first‐century audiences. The conference organizers anticipated that scientists, educators, exhibit professionals, and other members of the natural history community would identify and prioritize research questions about what, how, why, when, and where people learn about natural history. We prepared to engage in a conversation about how natural history museums could change what they do. The participants' overwhelming passion for their work, and for natural history museums and their transformative potential for society, quickly turned the conversation toward how natural history museums should change what they are. The result was an emergent learning research agenda situated within a broader vision for natural history museums.